Predictive value of positional change in vital capacity to identify diaphragm dysfunction - Brault, Marilyne; Gabrysz-Forget, Fanny; Dubé, Bruno-Pierre (Respiratory physiology & neurobiology, 2021)
•A decrease in vital capacity in the supine position is characteristic of diaphragm dysfunction.•The fall in vital capacity allows the identification of bilateral diaphragm weakness with high sensitivity and specificity.•For unilateral diaphragm weakness, the fall in vital capacity is too variable to serve as a predictive or diagnostic tool. Sitting-to-supine fall in vital capacity (ΔVC) can be used to help identify diaphragm dysfunction (DD), but its optimal predictive threshold value is uncertain. Our aim was to evaluate the diagnostic performance of ΔVC in identifying the presence of unilateral or bilateral DD. Patients referred to the diaphragm dysfunction clinic of our center (2017–2018) were included. All subjects had lung function testing (including measurement of ΔVC) and an ultrasound assessment of diaphragm thickening fraction (TFdi). Unilateral DD was defined as a single hemidiaphragm with TFdi ≤30 % and bilateral DD as a mean TFdi value of both hemidiaphragms ≤30 %. Clinical and physiological characteristics were compared across groups, and sensitivity/specificity analyses of ΔVC to identify DD were performed. 84 patients were included (31 unilateral DD, 17 bilateral DD and 36 without significant DD). DD groups had similar age, gender and BMI (all p > 0.05), but patients with bilateral DD had lower FVC, FEV1, MIP, TLC, ΔVC and more frequent orthopnea than patients with unilateral DD (all p < 0.05). There was a significant correlation between TFdi and ΔVC (rho=-0.56, p < 0.001). The optimal ΔVC value to identify bilateral DD was ≤-15 % [AUC 0.97 (95 %CI 0.89−1.00), p < 0.001, with sensitivity and specificity of 100 % and 89 %, respectively]. No single threshold of ΔVC could accurately predict unilateral DD [AUC 0.58 (95 %CI 0.45−0.72), p = 0.24]. ΔVC performs poorly in identifying patients with unilateral DD. However, a ΔVC value ≤-15 % is strongly associated with the presence of bilateral DD. These findings should be taken into account when using ΔVC in the evaluation of patients with suspected DD.